PENGEMBANGAN MEDIA APLIKASI PEMBELAJARAN GERBANG LOGIKA DASAR UNTUK MENINGKATKAN KREATIVITAS SISWA SEKOLAH MENENGAH KEJURUAN - Syahputra, Darma; Dewi, Happy Indira (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2025)
This study aims to develop a learning application media for basic logic gates that is feasible and effective for use in learning in vocational high schools. This study uses the Research and Development (R&D) method with the development of the ADDIE model. The subjects in this study were students and teachers of class X TITL SMK Negeri 1 Aceh Barat Daya. The data analysis technique used is qualitative quantitative analysis. The results of the study indicate that the learning application media is feasible for use based on testing by material experts with a score percentage of 91% "very feasible", media experts 94% "very feasible", the trial score for teacher use 93% "very feasible" and student trials with a score of 95% 'very feasible'. So it can be concluded that the basic logic gate learning application media is effective for use based on the results of the N-Gain calculation trial on students' pre-test and post-test scores showing an increase of 0.56 which means it is in the effective category (> 0.56 - 0.75). Based on the results obtained, this study can help teachers in the form of learning application media that is feasible for use and can increase student creativity.